The Influence of Brand Authenticity on Consumer Buying Behavior in Social Media Marketing - Maham Rao; Waqar Younas*; Muhammad Farooq; Muhammad Hassaan; Shan Zulfiqar, (Dialogue Social Science Review (DSSR), 2025)
In today’s digital age, social media platforms have revolutionized brand consumer interactions, positioning themselves as critical drivers of purchasing behavior. This study investigates the role of perceived brand authenticity on consumer buying decisions within social media marketing. Using a cross-sectional quantitative design, data was gathered from 50 active social media users through structured surveys. Descriptive and inferential analyses, including Chi-square tests, were applied to explore associations between variables. Findings reveal that 80% of respondents have purchased from brands on social media, with direct brand engagement showing a statistically significant relationship with buying behavior (p = 0.038). In contrast, the self-reported importance of authenticity did not exhibit a significant correlation with purchases. Results highlight that authentic action manifested through engagement and responsiveness rather than passive brand image , is the key driver of trust and consumer behavior. The study offers actionable insights for marketers on fostering trust through genuine, interactive strategies and leveraging user-generated content for business success. Keywords: Social Media Marketing, Brand Authenticity, Consumer Trust, Buying Behavior, User-Generated Content, Engagement